PERBANDINGAN KADAR ASAM URAT DAN LAJU FILTRASI GLOMERULUS (LFG) PADA PASIEN GAGAL GINJAL KRONIK SEBELUM DAN SESUDAH HEMODIALISA - ROJU LUBIS; ISRA THRISTY (LP2MTBM MAKARIOZ, 2023)
Chronic Kidney Disease (CKD) is a global health problem that affects more than 200 million people worldwide.1 According to the Global Burden of Disease Study (2010), CKD was ranked the 27th leading cause of death worldwide in 1990, the ranking is increasing to be ranked 18th in 2019. This shows an increase in the number of CKD sufferers in the last 2 decades. According to the latest data according to the 7th Report of the Indonesian Renal Registry, every year Indonesia experiences an increase in patients undergoing hemodialysis, it is estimated that there are 17,193 new patients and 11,689 active patients with a mortality rate of 2,221 in 2019. The aim of this study was to describe uric acid levels and glomerular filtration rate (GFR) in patients with chronic renal failure before and after hemodialysis. The study was a descriptive non-retrospective cross-sectional study using secondary data in the form of medical records to see uric acid levels and LFG values before and after hemodialysis at the Rashida Kidney Hospital. Furthermore, the data were collected and processed using the Paired T-Test. Results: The results of the study of uric acid levels in patients with before and after hemodialysis showed p = 0.011 (p <0.05) and the LFG Values before and after with the discovery test p = 0.000 (p <0.05). finding the value between the before and after values on uric acid levels and LFGvalues